Pirmojo Konstantino Sirvydo žodyno pavadinimas - Lukšaitė, Ingė (Knygotyra, 1995)
The title of the first dictionary by K. Sirvydas published about 1620 is not known as the only copy survived of it is defected. In the library list N 290 made by the famous culture figure S. Rysinski (date of birth unknown – november 18, 1625) the description of the dictionary title is given “Promptuarium dictionum Polonicarum Latinarum et Lithuanicarum”. After the identification of all present descriptions of the dictionary titles and the comparison with the authentic ones it was determined that in all descriptions S. Rysinski had exactly marked the main word of the title. The dictionary had to be “promptuarium” (“the granary”). The persons who compiled the dictionary S. Rysinski noted only for the Latin and Greek languages. He did not note them for the dictionaries of national languages. It’s not clear whether the name of K. Sirvydas was written in the title. The description beares the sequence of languages but it also can point out the structure of the dictionary but not the title. The conclusion might be drawn that the dictionary by K. Sirvydas of 1620 had a title “Promptuarium dictionum Polonicarum Latinarum et Lithuanicarum” (“The Granary of the Polich, Latin, Lithuanian Languages”). One more argument may support the thought that the dictionary of 1620 by K. Sirvydas was the first dictionary (with its own title and word register) and the dictionary of 1642 “Dictionarimn trium linguarum” was the second (with different title and separate register). It is not clear to which dictionary should the publication of 1631 be attached, untill a copy of this publication would be found.